Rhodiola rosea Linnaeus improves learning, memory, and symptoms of depression – an integrative review (Revista Contexto & Saúde, 2026)
Traditional antidepressants are associated with side effects that lead to treatment discontinuation. Natural alternatives have been studied, such as Rhodiola rosea (RR), for treating depression. This integrative review investigated the effects of RR in animals with induced depression to assess its effectiveness in alleviating depressive symptoms and improving learning and memory. The PubMed, Scopus, Web of Science, and ScienceDirect databases were searched for relevant studies using the terms “Salidroside,” “Rhodioloside,” “Rhodiola rosea,” “depression,” “depressive disorder,” “depression, chemical,” and “animal.” The RR extract and salidroside were evaluated in six and eight studies, respectively. RR extract and salidroside improve cognitive function, neuroplasticity, and serotonin and corticosterone levels in rats. Using Rhodiola rosea extract or salidroside improves learning and memory and reduces neuronal damage caused by depression.
Keywords: antidepressive agents; neurogenesis; “golden root”